The Link of Social Media and Brand Image On Consumer Purchase Intention the Mediating Role E-Wom - Ardani, Wayan (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2024)
Electronic Word of Mouth (E-WOM) is a form of marketing, where people provide information and make honest recommendations to other people about brands, products and services. E-WOM is a new concept from WOM which provides transparency and easy access to information via the internet. The aims of this research was to determine the role of e-WOM in mediating the influence of social media and brand image on consumer purchase intention on micro, small and medium enterprises (MSMEs). The research respondents were customers of MSMEs culinary sector in Denpasar. The size of respondents were 100 culinary customers, chosen by accidental sampling or the respondents were chosen by chance at the area and was considered appropriate as a information source. Within the survey, there were five choices of scores for each question that can be chosen concurring to the real circumstance felt by the respondent. The data were analyzed with the SmartPLS 3.0. The research revealed social media and brand image has a positive and significant both direct effect as well mediated by E-WOM on customer purchase intention. The results of this research can be as reference for MSMEs that social media, brand image, positive e-WOM are important factors to increased purchase intention.